Enhancing Young Learners' Creative Thinking through Problem-Based Learning: An Indonesian Early Childhood Education Context - sulistyawati, wiwik (Journal of Education Technology and Inovation, 2025)
ABSTRAK Background: Creative thinking has emerged as a critical 21st-century competency, yet Indonesian early childhood education continues to employ predominantly teacher-centered approaches that may constrain children's natural creative capacities during critical developmental periods. Purpose: This study examined the effectiveness of Problem-Based Learning (PBL) in enhancing creative thinking abilities among young learners in Indonesian early childhood education contexts, specifically investigating its impact on fluency, flexibility, originality, and elaboration dimensions. Method: A quasi-experimental design with non-equivalent control groups was employed involving 120 children aged 4-5 years from six early childhood centers in Jember Regency, East Java. Participants were allocated into experimental (n=60) and control (n=60) groups through cluster random sampling. The PBL intervention spanned twelve weeks with three 60-minute sessions weekly. Creative thinking was assessed using an adapted Torrance Tests of Creative Thinking-Figural Form (TTCT), complemented by classroom observations and portfolio assessments at pre-test, post-test, and eight-week follow-up. Results: ANCOVA results revealed significant main effects of PBL on post-test creative thinking scores after controlling for baseline performance (F(1,117) = 51.00, p < .001). The experimental group demonstrated substantially superior performance (M = 56.17, SD = 6.24) compared to controls (M = 51.34, SD = 7.05), with mean gains more than double (M = 8.15 vs. M = 3.59). Effects persisted at follow-up assessment (M = 54.85 vs. M = 50.05), indicating sustained retention. Dimensional analysis showed particularly pronounced impacts on originality and flexibility. Conclusion: Problem-Based Learning constitutes an efficacious pedagogical approach for enhancing creative thinking in Indonesian early childhood contexts when implemented with cultural responsiveness and appropriate scaffolding. The findings support PBL adoption as a mechanism for cultivating twenty-first-century competencies while demonstrating effectiveness across socioeconomic strata